Neuronal Properties, In Vivo Effects, and Pathology of a Huntington's Disease Patient‐Derived Induced Pluripotent Stem Cells123. (20th August 2012) - Jeon, Iksoo; Lee, Nayeon; Li, Jia‐Yi; Park, In‐Hyun; Park, Kyoung Sun; Moon, Jisook; Shim, Sung Han; Choi, Chunggab; Chang, Da‐Jeong; Kwon, Jihye; Oh, Seung‐Hun; Shin, Dong Ah; et al.
Abstract: Induced pluripotent stem cells (iPSCs) generated from somatic cells of patients can be used to model different human diseases. They may also serve as sources of transplantable cells that can be used in novel cell therapies. Here, we analyzed neuronal properties of an iPSC line derived from a patient with a juvenile form of Huntington's disease (HD) carrying 72 CAG repeats (HD‐iPSC). Although its initial neural inducing activity was lower than that of human embryonic stem cells, we found that HD‐iPSC can give rise to GABAergic striatal neurons, the neuronal cell type that is most susceptible to degeneration in HD. We then transplanted HD‐iPSC‐derived neural precursors into a rat model of HD with a unilateral excitotoxic striatal lesion and observed a significant behavioral recovery in the grafted rats. Interestingly, during our in vitro culture and when the grafts were examined at 12 weeks after transplantation, no aggregate formation was detected. However, when the culture was treated with a proteasome inhibitor (MG132) or when the cells engrafted into neonatal brains were analyzed at 33 weeks, there were clear signs of HD pathology. Taken together, these results indicate that, although HD‐iPSC carrying 72 CAG repeats can form GABAergic neurons and give rise to functional effects in vivo, without showing an overt HD phenotype, it is highly susceptible to proteasome inhibition and develops HD pathology at later stages of transplantation. These unique features of HD‐iPSC will serve as useful tools to study HD pathology and develop novel therapeutics. Stem Cells 2012;30:2054–2062